Polishing Pad
The polishing pad with controlled pore diameter and high slurry retention addresses non-uniformity issues, enhancing both site and global flatness by ensuring consistent polishing performance.
Patent Information
- Application Number
- JP2020211459
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-21
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2040-12-21
AI Technical Summary
Existing polishing pads for semiconductor substrates face issues with non-uniform pore diameters leading to variations in resin amount and stress, affecting site and global flatness, and poor slurry retention resulting in decreased polishing rate and convex shapes.
A polishing pad with a polyurethane resin foam having a pore filling rate of 80% or more and a controlled pore diameter difference of 120 μm or less, ensuring high slurry retention and uniform pore distribution.
The solution enhances slurry retention and uniform stress distribution, improving both site and global flatness of polished objects by maintaining consistent polishing speed and reducing local stress variations.
Smart Images

Figure 0007608146000001 
Figure 0007608146000002 
Figure 0007608146000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing pad. [Background technology]
[0002] In the mirror polishing process of polishing objects such as silicon wafers used as semiconductor substrates, urethane foam polishing pads made of polyurethane resin foam are widely used. In recent years, the demand for flattening properties of polishing objects has been increasing in order to improve the yield of semiconductor chip products.
[0003] A urethane foam polishing pad has many roughly spherical cavities (hereinafter also referred to as "pores"). In particular, the pores that open on the surface have functions such as holding the slurry and forming minute contact points with the workpiece to be polished. The pore structure is characterized by the size and number distribution, the proportion of closed cells and open cells (hereinafter also referred to as "communicating pores"), etc., and various polishing pads have been proposed for controlling these.
[0004] For example, Patent Document 1 discloses a polishing pad that achieves a good balance between the slurry retention and the rigidity of the polishing layer by adjusting the proportion of interconnected pores. Patent Document 2 discloses a polishing pad that improves the flatness of the workpiece and suppresses edge drooping by increasing the proportion of interconnected pores.
[0005] Furthermore, Patent Document 3 discloses a polishing pad that does not contain large pores and uses unfoamed heat-expandable microspheres so as to have uniform pore diameters, thereby suppressing edge droop. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2015-193057 A [Patent Document 2] JP 2011-020234 A [Patent Document 3] JP 2010-274361 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the polishing pads of Patent Documents 1 and 2, the size of the pores is not controlled, and the pore diameter is not uniform, so the amount of resin around the pores varies. As a result, the amount of deformation during polishing and therefore the stress on the workpiece vary locally, which can cause deterioration of the site flatness of the workpiece.
[0008] On the other hand, the polishing pad of Patent Document 3 uses unfoamed heat-expandable microspheres to have uniform pore diameters, and the foam can only retain a small amount of slurry inside due to the shell of the heat-expandable microspheres. As a result, even if slurry is supplied to the pad surface during polishing, most of it is expelled due to the sliding of the polished object. As a result, the slurry is depleted toward the center of the polished object, the polishing speed decreases, and the center tends to have a convex shape, which causes a problem of deterioration in the global flatness of the polished object.
[0009] As described above, in order to improve both the site flatness and the global flatness of the polished object, it has been difficult to increase the proportion of communicating pores to improve the retention of the slurry while controlling the pore diameter uniformly.
[0010] In view of the above circumstances, an object of the present invention is to provide a polishing pad which has a high proportion of communicating pores to improve the retention of slurry and which allows the pore diameter to be controlled uniformly. [Means for solving the problem]
[0011] The polishing pad according to the present invention is a polishing pad comprising a polyurethane resin foam having a large number of pores formed therein, and the polyurethane resin foam satisfies the following requirements (1) and (2). (1) The filling rate of the pores with pure water is 80% or more. (2) The difference between the cumulative volume 84% diameter and the cumulative volume 16% diameter of the pores is 120 μm or less.
[0012] In such a polishing pad, the pores are filled with pure water at a rate of 80% or more, and the ratio of interconnected pores is increased to improve the retention of slurry. This allows sufficient slurry to be supplied to the center of the workpiece during polishing, and suppresses the decrease in polishing speed, thereby improving the global flatness of the workpiece.
[0013] In addition, in this polishing pad, the difference between the cumulative volume 84% diameter and the cumulative volume 16% diameter of the pores is 120 μm or less, so that the pore diameter can be controlled uniformly. This can be said to suppress the variation in local stress on the polished object and improve the site flatness of the polished object. Effect of the Invention
[0014] As described above, according to the present invention, it is possible to provide a polishing pad which has a high proportion of communicating pores, thereby improving the retention of slurry, and in which the pore diameter can be controlled to be uniform. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] Hereinafter, one embodiment of the present invention will be described.
[0016] The polishing pad according to this embodiment comprises a polyurethane resin foam having a large number of pores formed therein. The polyurethane resin foam satisfies the following requirements (1) and (2). (1) The filling rate of the pores with pure water is 80% or more. (2) The difference between the cumulative volume 84% diameter and the cumulative volume 16% diameter of the pores is 120 μm or less.
[0017] The filling rate of the pores with pure water is the ratio of the volume of water that penetrates the pores under water immersion to the total volume of the pores, and indicates the slurry retention during polishing. The higher the ratio of interconnected pores, the higher the filling rate of the pores with pure water, and the better the slurry retention.
[0018] In the polyurethane resin foam, the filling rate of the pores with pure water is 80% or more, and preferably 90% or more.
[0019] The filling rate of the pores with pure water is the apparent density of the pad (hereinafter referred to as the normal density ρ a ), and the apparent density of the pad in liquid (hereinafter referred to as the density in liquid ρ b ) where the normal density ρ a is obtained by dividing the pad weight by the pad volume. Also, the liquid density ρ b is obtained from the weight W' in the liquid when immersed in pure water by using Archimedes' principle, as shown in the following formula (i). If the pad is simply immersed in pure water, it will take a long time to fully wet the pores due to surface tension. Therefore, the pad is immersed in pure water for 10 minutes under reduced pressure of -0.1 MPa.
[0020]
number
[0021] If there are many interconnected pores and large pores that penetrate in the thickness direction, and no independent bubbles inside the pad, the submerged density will be equal to the resin true density. On the other hand, if there are only independent bubbles inside the pad, the submerged density will be smaller due to the buoyancy caused by the bubbles contained inside. From this difference, the filling rate can be calculated. Specifically, the filling rate is calculated by the following formula (ii).
[0022]
number
[0023] In the polyurethane resin foam, the porosity is preferably 45 to 75%, more preferably 50 to 70%, from the viewpoint of increasing the ratio of interconnected pores and improving the rigidity of the pad to improve flatness. The porosity is the ratio of the pore volume excluding the resin and the like to the pad volume, and can be measured using an X-ray CT scanner. That is, an X-ray CT scanner (e.g., TDM1000H-I manufactured by Yamato Scientific Co., Ltd.) is used to take a cross-sectional image (measurement range, for example, 1.6 mm x 1.6 mm x 0.7 mm) of the polyurethane resin foam in a direction perpendicular to the polishing surface. Then, the cross-sectional image is binarized using image processing software (e.g., VGStudioMAX 2.1 manufactured by VOLUME GRAPHICS Co., Ltd.) to clearly separate the pore portion and the matrix portion (portion other than the pore portion). Next, the porosity can be obtained by dividing the volume of the pore portion obtained by summing the volumes of the pores by the volume of the measurement range.
[0024] The difference between the cumulative 84% volume diameter and the cumulative 16% volume diameter of the pores indicates the width of the distribution based on the pore volume. The cumulative 84% volume diameter and the cumulative 16% volume diameter mean the diameters at 84% and 16%, respectively, of the total pore volume when the pores are arranged in ascending order and the volumes are accumulated. The smaller this difference is, the narrower the distribution width on a volume basis, that is, the pore diameter can be controlled uniformly. The cumulative 84% volume diameter and the cumulative 16% volume diameter of the pores can be calculated by measuring the volume of each pore using an X-ray CT scanner. That is, an X-ray CT scanner (e.g., TDM1000H-I manufactured by Yamato Scientific Co., Ltd.) is used to capture a cross-sectional image (measurement range is, for example, 1.6 mm x 1.6 mm x 0.7 mm) of the polyurethane resin foam in the direction perpendicular to the polished surface. The cross-sectional image is then binarized using image processing software (e.g., VGStudioMAX 2.1 manufactured by VOLUME GRAPHICS Co., Ltd.) to clearly separate the pore portion from the matrix portion (portion other than the pore portion). Next, the volume of each pore is measured, arranged in ascending order, and the volumes are accumulated. When the volumes are divided by the volume of the entire pore portion, the pore volumes that reach 84% and 16%, respectively, are identified. The diameters of true spheres with the same volume as this pore volume are defined as the accumulated volume 84% diameter and the accumulated volume 16% diameter.
[0025] In the polyurethane resin foam, the difference between the 84% cumulative volume diameter and the 16% cumulative volume diameter of the pores is 120 μm or less, preferably 110 μm or less, while the difference between the 84% cumulative volume diameter and the 16% cumulative volume diameter of the pores is preferably 20 μm or more.
[0026] In the polyurethane resin foam, the cumulative 50% volume diameter of the pores is preferably 150 μm or less. With this configuration, the amount of resin around the pores is reduced, and the occurrence of scratches can be reduced because the grinding waste is prevented from being caught between the object to be polished and the resin in the surface layer. On the other hand, the cumulative 50% volume diameter of the pores is preferably 30 μm or more from the viewpoint of preventing the open pores from collapsing due to the elongation of the resin during polishing. The cumulative 50% volume diameter of the pores can be calculated using an X-ray CT scanner, similarly to the cumulative 84% volume diameter and the cumulative 16% volume diameter.
[0027] By evaluating pores using the cumulative volume 50% diameter, the influence of large diameter pores that occupy a large volume can be taken into consideration compared to the conventional evaluation using the number average diameter.
[0028] The polyurethane resin foam is a cured product obtained by curing a polyurethane resin composition. The polyurethane resin composition contains a compound containing active hydrogen (hereinafter also referred to as an "active hydrogen compound") and a compound containing an isocyanate group (hereinafter also referred to as an "isocyanate compound"). That is, the polyurethane resin foam contains a polyurethane resin having a structure in which a first constituent unit of an active hydrogen compound and a second constituent unit of an isocyanate compound are alternately repeated via urethane bonding.
[0029] The active hydrogen compound is an organic compound having an active hydrogen group in the molecule that can react with an isocyanate group.Specific examples of the active hydrogen group include functional groups such as a hydroxyl group, a primary amino group, a secondary amino group, and a thiol group.The active hydrogen compound may have only one type of functional group in the molecule, or may have multiple types of functional groups.
[0030] Examples of the active hydrogen compound include polyol compounds having a plurality of hydroxy groups in the molecule, and polyamine compounds having a plurality of primary amino groups or secondary amino groups in the molecule.
[0031] Examples of the polyol compound include polyol monomers and polyol polymers.
[0032] Examples of the polyol monomer include linear aliphatic glycols such as 1,4-benzenedimethanol, 1,4-bis(2-hydroxyethoxy)benzene, ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, 1,8-octanediol, and 1,9-nonanediol; branched aliphatic glycols such as neopentyl glycol, 3-methyl-1,5-pentanediol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, and 2-methyl-1,8-octanediol; alicyclic diols such as 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, and water-added bisphenol A; and polyfunctional polyols such as glycerin, trimethylolpropane, tributyrolpropane, pentaerythritol, and sorbitol.
[0033] The polyol monomer is preferably ethylene glycol or diethylene glycol, from the viewpoints that it is likely to result in higher strength during reaction, that it is likely to result in higher rigidity of the polishing pad having the produced polyurethane resin foam, and that it is relatively inexpensive.
[0034] Examples of the polyol polymer include polyester polyol, polyester polycarbonate polyol, polyether polyol, polycarbonate polyol, etc. The polyol polymer also includes a multifunctional polyol polymer having three or more hydroxy groups in the molecule.
[0035] Examples of the polyester polyol include polyethylene adipate glycol, polybutylene adipate glycol, polycaprolactone polyol, and polyhexamethylene adipate glycol.
[0036] Examples of the polyester polycarbonate polyol include a reaction product of a polyester glycol such as polycaprolactone polyol with an alkylene carbonate, and a reaction product obtained by reacting ethylene carbonate with a polyhydric alcohol and then reacting the resulting reaction mixture with an organic dicarboxylic acid.
[0037] Examples of the polyether polyol include polytetramethylene ether glycol (PTMG), polypropylene glycol (PPG), polyethylene glycol (PEG), and ethylene oxide-added polypropylene polyol.
[0038] The polycarbonate polyols include reaction products of diols such as 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, polyethylene glycol, polypropylene glycol, or polytetramethylene ether glycol with phosgene, diallyl carbonate (e.g., diphenyl carbonate), or cyclic carbonate (e.g., propylene carbonate).
[0039] Other examples of the polyol compound include diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, tripropylene glycol, and polyethylene glycol having a molecular weight of 400 or less.
[0040] The polyamine compound may be 4,4'-methylenebis(2-chloroaniline) (MOCA), 4,4'-methylenedianiline, trimethylene Bis(4-aminobenzoate), 2-methyl-4,6-bis(methylthio)benzene-1,3-diamine, 2-methyl-4,6-bis(methylthio)-1,5-benzenediamine, 2,6-dichloro-p-phenylenediamine, 4,4'-methylenebis(2,3-dichloroaniline), 3,5-bis(methylthio)-2,4-toluenediamine, 3,5-bis(methylthio)-2,6-toluenediamine, 3,5-diethyltoluene-2,4-diamine, 3,5-diethyltoluene-2,6-diamine, trimethylene glycol-di-p-aminobenzoate, 1,2-bis(2-aminophenylthio)ethane, 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, and the like.
[0041] Examples of the isocyanate compound include polyisocyanate and urethane prepolymer.
[0042] Examples of the polyisocyanate include aromatic diisocyanates, aliphatic diisocyanates, and alicyclic diisocyanates.
[0043] Examples of the aromatic diisocyanate include tolylene diisocyanate (TDI), 1,5-naphthalene diisocyanate, xylylene diisocyanate, 1,3-phenylene diisocyanate, 1,4-phenylene diisocyanate, etc. Examples of the aromatic diisocyanate include diphenylmethane diisocyanate (MDI) and modified products of diphenylmethane diisocyanate (MDI).
[0044] Examples of modified diphenylmethane diisocyanate (MDI) include carbodiimide modified, urethane modified, allophanate modified, urea modified, biuret modified, isocyanurate modified, oxazolidone modified, etc. Specific examples of such modified products include carbodiimide-modified diphenylmethane diisocyanate (carbodiimide-modified MDI).
[0045] Examples of the aliphatic diisocyanate include ethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, and hexamethylene diisocyanate (HDI).
[0046] Examples of the alicyclic diisocyanate include 1,4-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, norbornane diisocyanate, and methylenebis(4,1-cyclohexylene) diisocyanate.
[0047] The urethane prepolymer is a polymer formed by bonding a polyol with a polyisocyanate, and has an isocyanate group as a terminal group.
[0048] As one aspect of the polishing pad according to this embodiment, the polyurethane resin composition preferably contains 4,4'-methylenebis(2-chloroaniline) (MOCA). The polyurethane resin composition preferably further contains a foam stabilizer dispersed in an incompatible manner. The term "incompatible" means that the foam stabilizer is incompatible when 10% by mass of the foam stabilizer is added to MOCA melted at 125°C.
[0049] Examples of such foam stabilizers include silicone surfactants, fluorine surfactants, and ionic surfactants. Among these, the foam stabilizer is preferably a silicone surfactant from the viewpoint of foam stabilization and fine foaming. Examples of silicone surfactants include polyether-modified silicone.
[0050] The foam stabilizer is believed to assist the dispersion of the polyurethane resin composition when the polyurethane resin composition is at a low viscosity in the early stage of the reaction. On the other hand, when the polyurethane resin composition is at a high viscosity in the later stage of the reaction, microphase separation proceeds, and an aggregated portion of the hard segment containing MOCA occurs. When this comes into contact with the foam film, the foam stabilizer concentration in that portion decreases due to incompatibility, causing instability. This, combined with the increase in the internal pressure of the bubbles accompanying the progress of the foaming reaction, is believed to facilitate communication with adjacent bubbles. However, since the polyurethane resin composition is sufficiently highly viscous, it is believed that the bubbles do not coalesce and become coarse. Therefore, it is believed that by including the foam stabilizer in the polyurethane resin composition, a structure in which the pores are interconnected while maintaining fine pores is obtained.
[0051] When the isocyanate compound is a urethane prepolymer, the content of the foam stabilizer is preferably 0.2 to 5% by mass with respect to the urethane prepolymer.
[0052] The polishing pad according to this embodiment is configured as described above. Next, an example of a method for manufacturing the polishing pad according to this embodiment will be described.
[0053] The polishing pad according to the present embodiment can be manufactured by, for example, a prepolymer method. Specifically, a urethane prepolymer having an isocyanate group as a terminal group, water as a foaming agent, a foam stabilizer, an active hydrogen compound as a curing agent, and a catalyst are mixed and polymerized to obtain a polishing pad having a polyurethane resin foam.
[0054] Examples of objects to be polished with the polishing pad according to this embodiment include silicon wafers, optical materials, semiconductor devices, hard disks, glass plates, and the like.
[0055] The polishing pad according to this embodiment is configured as described above and has the following advantages.
[0056] That is, the polishing pad according to this embodiment is a polishing pad having a polyurethane resin foam having a large number of pores formed therein, and the polyurethane resin foam satisfies the following requirements (1) and (2). (1) The filling rate of the pores with pure water is 80% or more. (2) The difference between the cumulative volume 84% diameter and the cumulative volume 16% diameter of the pores is 120 μm or less.
[0057] In such a polishing pad, the pores are filled with pure water at a rate of 80% or more, and the ratio of interconnected pores is increased to improve the retention of slurry. This allows sufficient slurry to be supplied to the center of the workpiece during polishing, and suppresses the decrease in polishing speed, thereby improving the global flatness of the workpiece.
[0058] In addition, in this polishing pad, the difference between the cumulative volume 84% diameter and the cumulative volume 16% diameter of the pores is 120 μm or less, so that the pore diameter can be controlled uniformly. This can be said to suppress the variation in local stress on the polished object and improve the site flatness of the polished object.
[0059] The polishing pad according to the present invention is not limited to the above embodiment. The polishing pad according to the present invention is also not limited by the above-mentioned action and effect. The polishing pad according to the present invention can be modified in various ways without departing from the gist of the present invention. EXAMPLES
[0060] Next, the present invention will be described more specifically with reference to examples and comparative examples.
[0061] (Examples 1 to 6) A prepolymer, water as a foaming agent, a foam stabilizer, a curing agent, and a catalyst were mixed in a closed system using a stirring blade, and the prepolymer was polymerized to obtain a polishing pad (φ25 mm × thickness 1.3 mm) that was a polyurethane resin foam. The above-mentioned materials were specifically as follows. The stirring was performed in a closed system to prevent the inclusion of coarse pores due to air entrainment. In addition, the foam stabilizer in each example was dispersed incompatible with the curing agent. Prepolymer: A urethane prepolymer made by combining polytetramethylene ether glycol (PTMG) and tolylene diisocyanate (TDI) and having an isocyanate group as a terminal group. Foam stabilizer: Silicone foam stabilizer SZ-1671 (manufactured by Dow Corning Toray) Hardener: 4,4'-methylenebis(2-chloroaniline) (MOCA) Catalyst: Tertiary amine catalyst
[0062] Comparative Example 1 Except for using a foam stabilizer that was compatible with and dispersed in the curing agent, a polishing pad was obtained in the same manner as in Example 1. Specifically, the following foam stabilizer was used. Foam stabilizer: Silicone foam stabilizer SF-2937F (manufactured by Dow Corning Toray Co., Ltd.)
[0063] (Comparative Examples 2 and 5) A polishing pad was obtained in the same manner as in Example 1, except that no foam stabilizer was used.
[0064] Comparative Example 3 A polishing pad was obtained in the same manner as in Comparative Example 2, except that stirring was performed in an open system.
[0065] Comparative Example 4 A polishing pad was obtained in the same manner as in Comparative Example 1, except that stirring was carried out in an open system.
[0066] The filling rate of the pores with pure water and the cumulative volume of each of the pores in the polishing pads of each Example and Comparative Example were measured by the method described above. The results are shown in Table 1.
[0067] Using the polishing pads of each of the Examples and Comparative Examples, polishing of an object to be polished was carried out under the following polishing conditions. Polished object: Etched wafer Polishing machine: DMS 20B-5P-4D, manufactured by Speed FAM Slurry flow rate: 5L / min Slurry type: NP6610 diluted with water (NP6610:water = 1:30 (volume ratio))
[0068] The flatness was evaluated by measuring the GBIR (Global Backside Ideal Range) ratio and SFQR (Site Front Least Square) ratio using a Nanometro 300TT-A (Kuroda Precision Industries, Ltd.). The GBIR ratio indicates the global flatness and is for the entire wafer surface defined except for the periphery. On the other hand, the SFQR ratio indicates the site flatness and is related to the flatness of a limited area of the wafer, which roughly corresponds to the area of the semiconductor components to be fabricated. The results are shown in Table 1.
[0069] [Table 1]
[0070] As can be seen from the results in Table 1, the polishing pads of each example have a pore filling rate of 80% or more of pure water, which increases the proportion of interconnected pores and improves the retention of slurry. In addition, the polishing pads of each example have a difference between the pore diameter at 84% cumulative volume and the pore diameter at 16% cumulative volume of 120 μm or less, which allows the pore diameter to be uniformly controlled.
[0071] As can be seen from the results of Examples 1 and 2, a polishing pad satisfying all of the constituent requirements of the present invention can improve the global flatness and site flatness of an object to be polished.
[0072] On the other hand, the polishing pads of each comparative example cannot retain the slurry well because the filling rate of the pure water in the pores is less than 80%. Also, the polishing pads of comparative examples 3 and 4 cannot control the pore diameter uniformly because the difference between the cumulative volume 84% diameter and the cumulative volume 16% diameter of the pores exceeds 120 μm.
[0073] As can be seen from the results of Comparative Examples 1, 2 and 4, polishing pads that do not satisfy the constituent requirements of the present invention cannot improve the global flatness and site flatness of the workpiece.
Claims
1. A polishing pad having a polyurethane resin foam having a large number of pores formed therein, The polyurethane resin foam satisfies the following requirements (1) and (2), The polishing pad, wherein the polyurethane resin foam is a cured product obtained by curing a polyurethane resin composition, and the polyurethane resin composition contains a foam stabilizer dispersed in an incompatible manner. (1) The filling rate of the pores with pure water is 80% or more. (2) The difference between the cumulative volume 84% diameter and the cumulative volume 16% diameter of the pores is 120 μm or less.
2. 2. The polishing pad according to claim 1, wherein the polyurethane resin foam has pores having a cumulative volume 50% diameter of 150 μm or less.
3. 3. The polishing pad according to claim 1, wherein the polyurethane resin foam has a porosity of 45 to 75%.
4. 4. The polishing pad according to claim 1, wherein the polyurethane resin foam is a cured product obtained by curing a polyurethane resin composition containing 4,4'-methylenebis(2-chloroaniline).
Citation Information
Patent Citations
Polishing pad and polishing method
JP2010135493A
Polishing pad
JP2010274361A
Polishing pad, method of manufacturing the same, and polishing method
JP2011005563A
Polishing pad
JP2011020234A
Abrasive pad and method for manufacturing the same
JP2015193057A